Visitor Behavior in Ecotourism in Bandar Lampung: A Cultural Semiotic Study on Ecotourism Destination Attributes - Gita Paramita Djausal,; Fahmi Tarumanegara,; Fitri Juliana Sanjaya,; Najwa Rizqia, (RETORIKA: Jurnal Ilmu Bahasa, 2025)
This study aims to analyze the influence of ecotourism destination attributes on visitors' intentions for visiting, revisiting, and recommending in Bandar Lampung. Using a cultural semiotics approach, this research focuses on the attributes present in ecotourism destinations and identifies and interprets signs, symbols, and meanings that may influence visitors' interest. This study adopts a mixed-methods approach that integrates both quantitative and qualitative elements. Interviews with visitors, managers, and local communities provide in-depth qualitative insights into their perceptions and experiences regarding the ecotourism destination. These qualitative data are then analyzed alongside the quantitative data to obtain a more comprehensive understanding of the influence of destination attributes on visitors' intentions. The survey, involving 116 respondents, used a research instrument containing 39 questions, designed based on purchase decision theory and marketing mix. Data analysis was conducted using descriptive statistics, correlation tests, and multinomial regression. The findings of this study reveal that visitors tend to interpret cultural symbols based on their personal experiences and social backgrounds. For example, some visitors associate certain symbols with modern values, while others understand them in the context of deeper traditions. Therefore, interpretations of cultural symbols can vary depending on individual perspectives, reflecting the complexity of understanding culture in a broader context. These findings also emphasize that visitor behavior iss greatly influenced by how they interpret symbols and meanings within the cultural ecosystem in Bandar Lampung. Furthermore, the study reveals how ecotourism attributes shape visitor experience and satisfaction, as well as the role of local cultural elements in deepening their understanding of ecotourism. Therefore, the findings of this study provide a significant contribution to the development of sustainable ecotourism, emphasizing the importance of cultural aspects in the design and management of nature-based tourism destinations